The prognostic nutritional index represents a novel inflammation-nutrition-based prognostic factor for nasopharyngeal carcinoma - Jiang, Yan-Ming; Huang, Shi-Ting; Pan, Xin-Bin; Ma, Jia-Lin; Zhu, Xiao-Dong (Frontiers in Nutrition, 2023)
Purpose This study explored the relationship between the prognostic nutritional index (PNI) and overall survival rate (OS) in patients with nasopharyngeal carcinoma (NPC), and established and validated an effective nomogram to predict clinical outcomes. Methods This study included 618 patients newly diagnosed with locoregionally advanced NPC. They were divided into training and validation cohorts at a ratio of 2:1 based on random numbers. The primary endpoint of this study was OS, progression-free survival (PFS) was the second endpoint. A nomogram was drawn from the results of multivariate analyses. Harrell’s concordance index (C-index), area under the receiver operator characteristic curve (AUC), and decision curve analysis (DCA) were used to evaluate the clinical usefulness and predictive ability of the nomogram and were compared to the current 8th edition of the International Union Against Cancer/American Joint Committee (UICC/AJCC) staging system. Results The PNI cutoff value was 48.1. Univariate analysis revealed that age (p < 0.001), T stage (p < 0.001), N stage (p = 0.036), tumor stage (p < 0.001), PNI (p = 0.001), lymphocyte-neutrophil ratio (NLR, p = 0.002), and lactate dehydrogenase (LDH, p = 0.009) were significantly associated with OS, age (p = 0.001), T-stage (p < 0.001), tumor stage (p < 0.001), N-stage (p = 0.011), PNI (p = 0.003), NLR (p = 0.051), and LDH (p = 0.03) were significantly associated with PFS. Multivariate analysis showed that age (p < 0.001), T-stage (p < 0.001), N-stage(p = 0.02), LDH (p = 0.032), and PNI (p = 0.006) were significantly associated with OS, age (p = 0.004), T-stage (<0.001), N-stage (<0.001), PNI (p = 0.022) were significantly associated with PFS. The C-index of the nomogram was 0.702 (95% confidence interval [CI]: 0.653–0.751). The Akaike information criterion (AIC) value of the nomogram for OS was 1142.538. The C-index of the TNM staging system was 0.647 (95% CI, 0.594–0.70) and the AIC was 1163.698. The C-index, DCA, and AUC of the nomogram demonstrated its clinical value and higher overall net benefit compared to the 8th edition of the TNM staging system. Conclusion The PNI represents a new inflammation-nutrition-based prognostic factor for patients with NPC. In the proposed nomogram, PNI and LDH were present, which led to a more accurate prognostic prediction than the current staging system for patients with NPC.